Comparing Three-dimensional and Two-dimensional Preoperative Planning for Lumbar Transpedicular Screw Placement: A Retrospective Study - Doğu, Hüseyin; Abdallah, Anas; Muçuoğlu, Ali O.; Demirel, Nail; Elmadağ, N. Mehmet (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Transpedicular screw (TPS) misplacement is still a nightmare for spine surgeons. Preoperative planning is one of the methods that a surgeon could use to minimize this complication. This study aims to compare the efficacy of three-dimensional (3D) and two-dimensional (2D) preoperative planning in posterior lumbar TPSs placement performed using the freehand technique.Patients and Methods Patients who underwent posterior TPSs placement for degenerative lumbar spondylolisthesis or spinal stenosis using the freehand technique between November 2021 and October 2022 were evaluated retrospectively. In total, 33 and 30 patients who met the inclusion criteria were consecutively operated on with preoperative 2D and 3D planning, respectively. The patients were divided into the 2D preoperative planning group (2DG) and 3D preoperative planning group (3DG) and the two groups were compared.Results Sixty-three patients were operated during the study period. There was no significant difference between the groups regarding blood transfusion, operation time, and radiation exposure. Although the accuracy of TPSs positioning was 94.2 and 96.5% in the 2DG and 3DG, respectively, the difference between the groups was not statistically significant. The upper facet joint violation rate was 12.8% (n = 20) in the 2DG versus 3.5% (n = 5) in the 3DG (p = 0.006). All L4 TPSs were inserted with their standard entry points without any modification (p < 0.0001; relative/risk ratio = 0.64). The modification rate was higher in L1, L2, and L5 TPSs (p < 0.0001; χ2 = 24.7).Conclusion For patients with degenerative lumbar diseases, 3D preoperative planning in posterior lumbar instrumentation surgeries performed with the freehand technique decreased the upper facet joint violation rate.
Keywords: transpedicular screws; lumbar spine; three-dimensional measurement accuracy; software; facet joint violation